Self-decisive algorithm for unconstrained optimization problems as in biomedical image analysis - Jaffar, Farah; Mashwani, Wali Khan; Al-marzouki, Sanaa Mohammed; Aamir, Nudrat; Abiad, Mohammad (Frontiers in Computational Neuroscience, 2022)
In this paper, a new technique is developed where image processing along with two-step quasi-Newton methods is used. It is well-known fact that medical informatics is an essential component in the perspective of health care. Image processing and imaging technology are the recent advances in medical informatics, it includes image content representation, image interpretation, image acquisition, etc, and focuses on image information in the medical field. For this purpose, an algorithm is developed based on the image processing method which uses principle component analysis to find the image value of a particular test function and direct the function towards its best method for evaluation. To validate the proposed algorithm two functions, The modified trigonometric and Rosebrock functions, are tested on variable space.